2010
DOI: 10.1071/nb10013
|View full text |Cite
|
Sign up to set email alerts
|

Improving the health of sex workers in NSW: maintaining success

Abstract: NSW has a diverse sex industry that is limited in its size by modest demand. There is no evidence that decriminalisation in 1995 increased the frequency of commercial sex in NSW. Though the largest sector, female brothels, is now mainly staffed by Asian women, condom use for vaginal and anal sex exceeds 99% and sexually transmissible infection rates are at historic lows. These gains are attributable to the long-term support of the NSW Department of Health in collaboration with the community-based Sex Workers O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 15 publications
2
41
1
1
Order By: Relevance
“…Independent business models were mostly Internet-based through the use of online classified advertisements and personal Web sites, a situation similar to indoor marketplaces in many industrialized nations. 19,20,25,26 Although all participants worked as independents, we noted variations in financial security, degree of autonomy in setting conditions on services provided, fees charged, and condom use. These variations affected people's experiences of violence and their prevention strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent business models were mostly Internet-based through the use of online classified advertisements and personal Web sites, a situation similar to indoor marketplaces in many industrialized nations. 19,20,25,26 Although all participants worked as independents, we noted variations in financial security, degree of autonomy in setting conditions on services provided, fees charged, and condom use. These variations affected people's experiences of violence and their prevention strategies.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,13,14 However, it is estimated that 80% of sex workers work in indoor settings, [15][16][17] with many working independently via the Internet. [18][19][20] Emerging research estimates that the prevalence of violence among indoor workers is between 25% and 66%. 1,12,21 Robbery, nonpayment, physical and sexual assault, deceptive condom removal, and exploitation by landlords and police are among the most common forms of violence in indoor settings.…”
mentioning
confidence: 99%
“…Female sex workers (FSW) in Sydney, Australia, have responded to occupational risk of HIV and sexually transmitted infections (STIs) by implementing almost universal condom use for vaginal sex with clients, resulting in rates of bacterial STI comparable to the general population 1. As a consequence, the incidence of genital gonorrhoea in FSW in Sydney has dramatically reduced from 440 cases per 100 women-years in 1980–1981 to 0.24 per 100 women-years in 2004–2006 2.…”
Section: Introductionmentioning
confidence: 99%
“…5 Decriminalization facilitates health promotion (Harcourt et al, 2010) and has been shown to improve occupational health and safety conditions (Pinwill, 1999), eradicate police corruption (Donovan, Harcourt, Egger & Fairley, 2001) and increase opportunities for workers to choose between types of employment, moderating the power of operators and allowing workers to organize in their own right (Sullivan, 2010). Decriminalization also increases the likelihood of sex workers reporting incidents of violence to police (New Zealand Government, 2008).…”
Section: Sex Workmentioning
confidence: 99%